INCOMPLETENESS AS A RISK FACTOR FOR DELAY IN RETURN OF MEDICAL RECORD FILES - Mochammad Malik Ibrahim; malik (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Complete and timely medical records play an important role in health services, according to SOP at Aisyiyah Siti Fatimah Hospital, which states that the return of medical record documents is 2x24 hours. Where the results in the introduction showed that there was an inaccuracy in the return time and incomplete filling in the discharge summary. Method: This study used quantitative analytical methods and a cohort design, and logistic regression analysis. The number of samples used was 70 medical record documents, and the research instrument used was a checklist. Results: There was an incomplete discharge summary with a percentage of 67.1% while the return documents were not on time there were 51.4% and the RR value = 15.714 which was proven to affect the delay in returning medical record documents was the incompleteness of the discharge summary form, there was a probability value of 70% indicating that the incomplete discharge summary had a probability of inaccurate return. Conclusion: There is still an incomplete discharge summary form and a late return of medical record documents. Therefore, researchers can suggest that hospitals hold regular outreach regarding the importance of completeness and timeliness of returning medical record documents.